HIV STATUS AS A MITIGATING FACTOR IN SENTENCING: A CRITICAL REVIEW S v Magida 2005 2 SACR 591 (SCA) - Suhayfa Bhamjee; Ann Strode (Obiter, 2022)
Crime and punishment have always gone hand in hand. Over the centuries, courts have struggled with the difficult task of finding appropriate sentences. In doing so, they have had to deal with moral, social and other issues whilst striving to find a balance between society’s right to have justice done, and the offender’s right not to face an unnecessarily harsh sentence (S v Calitz 2003 1 SACR 116 SCA 121I-J). The rationale behind any particular sentence has historically been retributive (the court in pronouncing a sentence and imposing it, exacts the community’s lust for “revenge” in a legally sanctioned manner); preventative (once removed from free society, the offender is prevented from continuing to behave in the socially reprehensible manner for which he or she was convicted); reformative (once in custody of the correctional service authorities, the offender will be given the opportunity to reform, returning to society as a better citizen); and deterrent (the sentence imposed upon the offender discourages others from embarking on the criminal path (S v Khumalo 1984 3 SA 327 (A) 330D-E ). In a recent decision by the Supreme Court of Appeal, S v Magida (2005 2 SACR 591 (SCA)), the court held that the appellant was entitled to a lesser sentence because she was HIV-positive, had developed full-blown AIDS and could die soon (par 21). This case is significant as it is the first time the Supreme Court of Appeal has dealt with the circumstances in which HIV status ought to be a mitigating factor in sentencing. Whilst it is argued that the court’s decision is correct, it is regrettable that the court glossed over the complexities relating to HIV status as a mitigating factor.